Seasonal medicine shortages and pharmaceutical supply resilience in China: risk identification and policy optimization - Jieying Zhang; Caixia Liu; Lei Gu; Yuhan Zhang; Ningying Mao; Jun Li; Yafei Lan (BMC Public Health, 2026)
Abstract Background Climate change and seasonal disease patterns are placing growing pressure on medicine supply assurance. Although China has established policies on risk identification, stockpiling, production capacity adjustment, market supervision, and enterprise compliance, seasonal medicine shortages remain challenging due to fragmented policy implementation and limited coordination across the pharmaceutical supply chain. Objective This study aimed to identify risks of seasonal medicine shortages in China and propose policy options for strengthening pharmaceutical supply resilience. Methods A structured document-based review was conducted using official disease control information, clinical guidelines, expert consensus documents, policy documents, and publicly available reports on medicine supply problems. A stepwise selection approach was used. First, seasonal diseases were identified according to epidemiological characteristics and peak occurrence periods. Second, these diseases were matched with preventive or therapeutic medicines based on clinical guidelines, expert consensus statements, or official treatment recommendations. Third, medicines requiring priority supply assurance were further screened based on publicly reported previous supply problems. Results A total of 62 seasonal diseases were identified and matched with 140 medicines used for their prevention or treatment; 41 medicines were further identified as requiring priority supply assurance. Infectious and parasitic diseases were the largest group (32/62, 51.6%), followed by injury, poisoning and other external causes (10/62, 16.1%) and respiratory diseases (8/62, 12.9%). Monthly disease peaks were most concentrated in July and August. Among the 140 matched medicines, chemical drugs and biological products predominated (135/140, 96.4%), and antimicrobial drugs were the largest medicine category (42/140, 30.0%). Antimicrobial drugs remained the largest subgroup (13/41, 31.7%). Production-related supply disruption was the most frequent shortage-risk mechanism (23/41, 56.1%), followed by demand surge and active pharmaceutical ingredient (API) supply disruption (14/41 each, 34.1%). Conclusions This study provides an operational pathway for linking seasonal disease patterns, corresponding medicines, peak-demand periods, and previously reported supply problems. This pathway translates the broad policy goal of seasonal medicine supply assurance into specific targets for monitoring and preparedness, including priority diseases, core medicine categories, peak-demand periods, and medicines requiring closer attention. Multi-node monitoring, tiered reserve management, cross-regional allocation, flexible production capacity, policy coordination, and risk communication may strengthen pharmaceutical supply resilience.